2014
DOI: 10.1186/1471-2377-14-4
|View full text |Cite
|
Sign up to set email alerts
|

The eleventh reported case of Mulvihill-Smith syndrome in the literature

Abstract: BackgroundThe Mulvihill-Smith Syndrome was first recognized in 1975. After the recognition of the Mulvihill-Smith Syndrome, ten cases have been described.Case presentationThis article describes the eleventh case of this syndrome in a male patient, 24 years-old with short stature and microcephaly with mild cognitive impairment, deafness and allergic conjunctivitis. The patient was hospitalized several times for repeated infections, and the presence of multiple melanocytic nevi on his skin was noticed.Conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…There are only about 11 cases described in the literature. 6 This is the first report of retinal features in MSS. These ocular changes coincided with other systemic degeneration including mental and cognitive impairment, sensorineural hearing loss, and sleep disorder with the onset of adulthood.…”
Section: Discussionmentioning
confidence: 91%
“…There are only about 11 cases described in the literature. 6 This is the first report of retinal features in MSS. These ocular changes coincided with other systemic degeneration including mental and cognitive impairment, sensorineural hearing loss, and sleep disorder with the onset of adulthood.…”
Section: Discussionmentioning
confidence: 91%
“…[5] Agenesis of the second premolars and the right maxillary central incisors and poor oral health condition were reported in the eleventh case of Mulvihill–Smith syndrome in the literature. [14]…”
Section: Resultsmentioning
confidence: 99%
“…The first case was described in 1975 [4] and the last in 2011. [14] Seven of the patients were male and 4 were female, and the median age of the subjects was 17 years (range: 4–30). The demographic features of the study population are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations